BIBLIOMETRIC ANALYSIS OF RESEARCH ON THE EMPLOYABILITY SKILLS OF VOCATIONAL COLLEGES GRADUATES IN CHINA - Fan , Xiaohui1; Mohd Noor, Asma Lailee (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Since the fast development of vocational education and rapid enrollment of vocational college students in China, how to improve the students’ employability skills has aroused a lot of attention among the whole society. This paper employed bibliometric method to conduct a systematic analysis of research literature on the employability skills of vocational college graduates indexed by CNKI in China from 2000 to 2024. Through keyword co-occurrence analysis, author collaboration network analysis, institutional distribution analysis, and research hotspot evolution analysis, it revealed the current state, development trends, and future directions of research in employbility skills field. This study found that research on the employability skills of vocational college graduates is still an ongoing research gap concerning persons, the labor market, and vocational colleges. Moreover, the transfer of graduates’ employability skills under the fast development of artificial intelligence necessitates immediate focus from the academic community.